Analisis Wacana Kritis Teori Teun Van Dijk Pada Iklan YouTube Holisticare ID Berjudul “Jalur Pulang” - Fathiah Riadianti; Atikah Supiyah Ansoriyah; Wulan Nurhasanah; Rindy Antika; M. Oky Fardian Gafari; Mustika Wati Siregar (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2024)
Holisticare's advertisement entitled "Path of Home (Ramadan Short Movie)" generally tells the story of a mother and child who are eager to go home for Eid. The aim of this research is to analyze and explain the hidden meaning behind the holisticare advertisement "Jalan Pulang" using three elements, namely; macro structure, superstructure and micro structure. The method used in this research is to use an in-depth content analysis technique of an advertisement with a qualitative descriptive approach. The data used is text or speech discourse in the Holisticare ID advertisement entitled "Path to Home". Data analysis was carried out using the Van Dijk model of critical discourse analysis theory which divides discourse into three parts: macro structure, superstructure and micro structure. Data collection techniques used include: techniques for listening, taking notes and documenting data from the advertisement entitled "The Way Home".